PENDEKATAN PSIKOLOGIS DALAM MENENTUKAN MINAT BERWIRAUSAHA MAHASISWA - I Gst. A.Kt. Gd Suasana; I Gde Ketut Warmika (EKUITAS (Jurnal Ekonomi dan Keuangan), 2023)
Entrepreneurship plays a real role in economic development and job creation. Research purposes; explain the influence of psychological factors on the interest in entrepreneurship, and find the best combination model of psychological factors that can be used as a predictor of interest in entrepreneurship. Respondents were students who had or were taking entrepreneurship courses at FEB Unud. The sample size was determined as many as 120 people by purposive sampling and data were analyzed using multiple linear regression. Analysis of the enter method found that psychological factors had a significant effect on entrepreneurial interest, and only the need for achievement and internal locus of control had a positive and significant effect on entrepreneurial interest. Based on the stepwise method, it was found that the combination of need for achievement, internal locus of control, and tolerance for ambiguity is the best predictor of entrepreneurial interest. The implication is that strengthening psychological factors for students can be approached with entrepreneurial motivation training by involving successful entrepreneurial role models. Future researchers, need to examine and identify other psychological factors, to further strengthen the results of the analysis, such as creativity and communication.